2020
DOI: 10.1101/2020.06.22.20136838
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

First results from the UK COVID-19 Serology in Oncology Staff Study (CSOS)

Abstract: Background: The global SARS-CoV-2 (COVID-19) pandemic has caused substantial worldwide mortality. At present, there is no data regarding oncologist-specific SARS-CoV-2 infection/immunity rates in the United Kingdom (UK) which might impact planning for the management of potentially immunosuppressed cancer patients. Here, we present the first results from the COVID-19 Serology in Oncology Staff (CSOS) study with the aim of informing non-surgical oncology management guidelines. Methods: Patient-facing staff work… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…• Several studies report an association between COVID-19 symptoms and: seropositivity [87][88][89], higher titres of IgG [29,79,90] and anti-RBD and anti-S antibodies [91]. • Two studies reported that asymptomatic healthcare workers did develop antibodies [92,93].…”
Section: Symptom Profilementioning
confidence: 99%
“…• Several studies report an association between COVID-19 symptoms and: seropositivity [87][88][89], higher titres of IgG [29,79,90] and anti-RBD and anti-S antibodies [91]. • Two studies reported that asymptomatic healthcare workers did develop antibodies [92,93].…”
Section: Symptom Profilementioning
confidence: 99%
“…Three studies report an association between COVID-19 symptoms and seropositivity, [156][157][158] and with higher titres of IgG, 29,159 IgA, 159 and anti-RBD and anti-S antibodies. 160…”
mentioning
confidence: 99%
“… Representativeness Is the data representative for HCW worldwide? Abdelmoniem et al [ 23 ] Low RoB Lacking representativeness Al-Zoubi et al [ 24 ] Low RoB Lacking representativeness Armin et al [ 25 ] Low RoB Lacking representativeness Brown et al [ 26 ] Low RoB Potentially for hospital staff, wide range of diverse job roles Campbell et al [ 27 ] Low RoB Lacking representativeness Cavicchiolo et al [ 28 ] Low RoB Lacking representativeness Demmer et al [ 29 ] Low RoB Lacking representativeness Dillner et al [ 30 ] Low RoB Potentially for hospital staff, high case number Fakhim et al [ 31 ] Low RoB Lacking representativeness Favara et al [ 32 ] Low RoB Lacking representativeness Ferreira et al [ 33 ] Low RoB Potentially for hospital staff, high case number Fusco et al [ 34 ] Low RoB Lacking representativeness Guery et al [ 35 ] Low RoB Lacking representativeness Halbrook et al [ <...…”
Section: Resultsmentioning
confidence: 99%